Roadmap for Building a National Trade Information Portal - United Nations Conference on Trade; Development (United Nations, 2022)
The present publication “Roadmap for Building a National Trade Information Portal” sets out the importance of placing the trader at the center as the primary customer and how a Trade Information Portal's system should be structured to ensure that the needed trade information is packaged and delivered, and received in a manner that is always easy to follow. The guidance set out in this document reaffirms that a central repository for trade information is the most effective way of complying with article 1 of the WTO Trade Facilitation Agreement, and that step-by-step guides to procedures are key to ensure transparency and work on making trade-related procedures more efficient.